2013
DOI: 10.1021/am4005623
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Breakdown in Silica–Amorphous Polymer Nanocomposite Films: The Role of the Polymer Matrix

Abstract: The ultimate energy storage performance of an electrostatic capacitor is determined by the dielectric characteristics of the material separating its conductive electrodes. Polymers are commonly employed due to their processability and high breakdown strength; however, demands for higher energy storage have encouraged investigations of ceramic-polymer composites. Maintaining dielectric strength, and thus minimizing flaw size and heterogeneities, has focused development toward nanocomposite (NC) films; but resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 33 publications
5
64
0
Order By: Relevance
“…This compliments similar studies of low permittivity contrast systems (e.g. silica NPs and polystyrene; silica NPs and poly methyl methacrylate 21,22 ), where the breakdown strength trends of HNPs and blends were comparable with inorganic loading and depended on the relative breakdown strength of the nanoparticle and matrix. In concert with E BD , an appreciable reduction in dielectric loss (up to 1 order of magnitude) was observed for all HNP assemblies, regardless of relative permittivity matching.…”
Section: Original Research Papersupporting
confidence: 87%
“…This compliments similar studies of low permittivity contrast systems (e.g. silica NPs and polystyrene; silica NPs and poly methyl methacrylate 21,22 ), where the breakdown strength trends of HNPs and blends were comparable with inorganic loading and depended on the relative breakdown strength of the nanoparticle and matrix. In concert with E BD , an appreciable reduction in dielectric loss (up to 1 order of magnitude) was observed for all HNP assemblies, regardless of relative permittivity matching.…”
Section: Original Research Papersupporting
confidence: 87%
“…An interesting observation is that the breakdown strength in the titania nanocomposites decreases with titania content up to 0.5 wt%, with subsequent increase with increasing filler content up to 10 wt%, although it remains lower than the breakdown strength of the pure epoxy. Grabowski et al [12] investigated the dielectric strength of silica nanocomposites, based on four different amorphous polymers with up to 45 vol% of silica. Where the breakdown strength increased initially in some of the nanocomposites, the breakdown strength of all nanocomposites decreased after the addition of 15 vol% and higher, again due to reaching the percolation threshold.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…When effects of percolation are considered, the work of Grabowski et al [12] has shown that adding up to 45 vol% of silica in polymethyl methacrylate (PMMA) significantly reduced the breakdown strength from * 800 to * 340 kV/mm. An increase in breakdown strength was reported by Siddabattuni et al [13] in 5 vol% epoxy/TiO 2 and epoxy/BaTiO 3 nanocomposites, containing surface modified titania and barium titanate nanoparticles followed by a drastic reduction in breakdown strength at percolation when 15 and 30 vol% of particles were added.…”
Section: Introductionmentioning
confidence: 99%
“…This relaxation process was pronounced for filler loadings > 6 %, where particle aggregation was observed. In another study [18] colloidal nano-silica was used to give good particle dispersion and it was noted that the permittivity and dielectric loss increased in the nanocomposites, relative to the unfilled host polymer, but in some systems the dielectric breakdown strength could be improved. Polypropylene (PP) systems containing an impact modifier (SEBS) plus maleic anhydride grafted PP have also been studied [19].…”
mentioning
confidence: 99%